Moderation - Castillo, Elaine (Viking, 2025)
"A bold and inventive novel about real romance in the virtual workplace -- bringing Castillo's trademark wit and sharp cultural criticism to an irresistible story about the possible future of love. Girlie Delmundo is the greatest content moderator in the world, and despite the setbacks of financial crises, climate catastrophe, and a global pandemic, she's going places: she's getting a promotion. Now thanks to her parent company Paragon's purchase of Fairground -- the world's preeminent virtual reality content provider -- she's on the way to becoming an elite VR moderator, playing in the big leagues and, if her enthusiastic bosses are to be believed, moderating the next stage of human interaction. Despite the isolation that virtual reality requires from colleagues, friends, and family, the unbelievable perks of her new job mean she can solve a lot of her family's problems with money and mobility. She doesn't have to think about the childhood home they lost back in the Bay Area, or history at all -- she can just pay any debts that come due. But when she meets William Cheung, Playground's wry, reticent co-founder (now Chief Product Officer) and slowly unearths some of his secrets, and finds herself somehow falling in love, she'll learn that history might be impossible to moderate and the future utterly impossible to control."--